The Role of Cognitive and Affective Corporate Reputation in Investor Behavior: An Empirical Investigation in Egyptian Stock Exchange Market - Marzouk, Wafaa Galal (Journal of Research in Marketing (ISSN: 2292-9355), 2016)
The aim of this empirical study is to examine the perceptions of individual investors in the stock market in Egypt of the construct of corporate reputation and to test the linkages between perceived corporate reputation, perceived trust, affective commitment and investor behavioral outcomes. This study extents the view beyond the cognitive corporate reputation and shed light on the role of affective corporate reputation on investor’s behavioral outcomes. Five hypotheses were tested on a sample of 220 individual investors in Egyptian stock exchange market out of 384 distributed, giving a response rate of 55 per cent. Partial least squares structural equation modeling tool (PLS-SEM) was used to assess the relationships among variables under investigation. The study results confirm that perceived corporate reputation of an individual investor has an important role in explaining his/her behavioral outcomes. Specifically, the results clearly indicated that the cognitive dimension not only dominates in the corporate reputation construct but also has an impact on behavioral outcomes. Furthermore, the finding confirms that affective corporate reputation is a dimension relevant to the reputations of companies; however, its contribution is relatively low compared to cognitive dimensions of corporate reputation in influencing the behavioral outcomes of investors. The results additionally show the direct and multiple mediated effects that link cognitive and affective corporate reputation to investor trust, affective commitment, and investor behavioral outcomes. In particular, the empirical results of this study provide evidence of the positive and significant effect of reputation on behavioral outcomes through the investor trust. However, the study’s findings also provide evidence that the indirect relation between affective corporate reputation and investor behavioral outcomes is not straightforward. As a mediator, only investor trust mediates the impact of affective corporate reputation on investor behavioral outcomes, but it is not a strong effect.